2018
DOI: 10.3389/fimmu.2018.02566
|View full text |Cite
|
Sign up to set email alerts
|

The Role of NLRP3 and IL-1β in the Pathogenesis of Inflammatory Bowel Disease

Abstract: It is logical to assume that a major pro-inflammatory mechanism, i.e., the NLRP3 inflammasome would play a prominent role in the pathogenesis of the Inflammatory Bowel Disease (IBD) in humans. However, while both studies of murine models of gut disease and patients provide data that the main cytokine product generated by this inflammasome, IL-1β, does in fact contribute to inflammation in IBD, there is no evidence that IL-1β plays a decisive or prominent role in “ordinary” patients with IBD (Crohn's disease). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
134
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(138 citation statements)
references
References 47 publications
3
134
0
1
Order By: Relevance
“…Together, these studies highlight the complexity of NLRP3 inflammasome responses and downstream mediators in Crohn's disease, and indicate important potential avenues of investigation that examine the effects of gain‐ and loss‐of‐function mutations in NLRP3 that can result in hyperproduction and hypoproduction of IL‐1 family cytokines, respectively (reviewed in Refs. 51 and 52 ). These data support a rationale for assessing dysfunctional NLRP3 inflammasome‐driven responses in IBDs.…”
Section: Nlrp3 Inflammasomes In the Gutmentioning
confidence: 98%
“…Together, these studies highlight the complexity of NLRP3 inflammasome responses and downstream mediators in Crohn's disease, and indicate important potential avenues of investigation that examine the effects of gain‐ and loss‐of‐function mutations in NLRP3 that can result in hyperproduction and hypoproduction of IL‐1 family cytokines, respectively (reviewed in Refs. 51 and 52 ). These data support a rationale for assessing dysfunctional NLRP3 inflammasome‐driven responses in IBDs.…”
Section: Nlrp3 Inflammasomes In the Gutmentioning
confidence: 98%
“…Increased expression of NLRP3 and secretion of IL-1β. Downregulation of NLRP6, NLRP12 (Mao et al, 2018) Rheumatoid arthritis Both (arterial and venous types). Due to endothelial injury and hypercoagubility.…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…19 Dysregulated NLRP3 inflammasome activation is involved in diverse diseases, including neurodegenerative diseases, 20,21 osteoarthritis, 22 cancer, 23,24 and inflammatory diseases. 25,26 Few studies have investigated the relationship between NLRP3 inflammasome activation and IVDD. However, numerous studies have confirmed that IL-1β is an important cause of IVDD, 16,27 and so we hypothesized that the NLRP3 inflammasome activation/IL-1β inflammatory response axis may play an important role in IVDD progression and that eliminating stimuli that activate the NLRP3 inflammasome may alleviate this progression.…”
Section: Introductionmentioning
confidence: 99%